2014
DOI: 10.3390/ijerph110404140
|View full text |Cite
|
Sign up to set email alerts
|

Social Cost of Leptospirosis Cases Attributed to the 2011 Disaster Striking Nova Friburgo, Brazil

Abstract: The aim of this study was to estimate the social cost of the leptospirosis cases that were attributed to the natural disaster of January 2011 in Nova Friburgo (State of Rio de Janeiro, Brazil) through a partial economic assessment. This study utilized secondary data supplied by the Municipal Health Foundation of Nova Friburgo. Income scenarios based on the national and state minimum wages and on average income of the local population were employed. The total social cost of leptospirosis cases attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…The findings show that the number of HE is associated with the rates and hospitalization in both regions; however, we observed that in the periods where more than 15 HE occurred in a single month, a significant increase was observed with greater repercussions in macro health regions with greater proximity to the coast ( Figure 5). This is in accordance with other studies for Brazil, South America and other countries [12,22,23].…”
Section: Correlation Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…The findings show that the number of HE is associated with the rates and hospitalization in both regions; however, we observed that in the periods where more than 15 HE occurred in a single month, a significant increase was observed with greater repercussions in macro health regions with greater proximity to the coast ( Figure 5). This is in accordance with other studies for Brazil, South America and other countries [12,22,23].…”
Section: Correlation Analysissupporting
confidence: 94%
“…On the other hand, floods have been reported to be associated with the increase of the global burden of disease [12], morbidity [13], mortality [14,15], social and economic disruptions. Regarding flood-related morbidities, an expressive number of articles has been published on the analysis of episodes of waterborne diseases related to the contamination of foods ingested, leading to the emergence of cases of Leptospirosis [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Strain emergence or re-emergence in a given area is likely to occur due to changing environments, host population fluctuations and vaccine pressure. Detecting such a change would facilitate appropriate leptospirosis preparedness efforts and would be useful in preparing for natural disasters, such as storms, hurricanes and particularly flooding, all of which are usually associated with an increased incidence of human and animal leptospirosis [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ressalta-se a importância da atenção às áreas detectadas com taxas estimadas elevadas neste estudo, para um aprimoramento da vigilância de leptospirose, pois são áreas que têm características ecológicas sugestivas de maior risco, mas talvez o serviço de vigilância não esteja sendo tão eficiente na detecção destes casos. Devido provavelmente a esses fatores, observa-se no Brasil uma incidência de leptospirose baixa e uma letalidade alta 33 Este estudo permitiu um melhor conhecimento da ecologia de transmissão da leptospirose. Além da importância das inundações e dos problemas no esgotamento sanitário discutidos anteriormente, destacam-se também as condições socioeconômicas baixas representadas pela proporção de chefes de família com pelo menos dez anos de estudos, a proporção da população residente em área de favela e problemas relacionados ao saneamento ambiental 33 .…”
Section: Principais Achadosunclassified
“…Devido provavelmente a esses fatores, observa-se no Brasil uma incidência de leptospirose baixa e uma letalidade alta 33 Este estudo permitiu um melhor conhecimento da ecologia de transmissão da leptospirose. Além da importância das inundações e dos problemas no esgotamento sanitário discutidos anteriormente, destacam-se também as condições socioeconômicas baixas representadas pela proporção de chefes de família com pelo menos dez anos de estudos, a proporção da população residente em área de favela e problemas relacionados ao saneamento ambiental 33 .…”
Section: Principais Achadosunclassified